Implications Of Polygamy Practices On Positive Law In Indonesia - Jaman, Najmah (Prophetic Law Review, 2020)
Polygamy is a form of marriage that often leads to polemics in the society despite the fact that the concept of polygamy in Islamic law is basically permissible if the husband acts fairly. However, in terms of positive law, to have a polygamous marriage, a husband must get permission from the court under limited justifications and strict conditions. Without the legal permission from the court, the practice of polygamy will have implications in the positive law in Indonesia. Therefore, the purpose of this study is to apprehend the implications of the practice of polygamy on positive law in Indonesia. The result is that Practices of Polygamy may have an impact on the Indonesian criminal and civil law system.Keywords: Polygamy; Islamic law; Positive lawImplikasi Praktek Poligami Terhadap Hukum Positif Di IndonesiaAbstrakPoligami merupakan salah satu bentuk perkawinan yang sering menimbulkan polemik di masyarakat, padahal konsep poligami dalam hukum Islam pada dasarnya diperbolehkan jika suami dapat berlaku adil. Namun dari segi hukum positif, untuk melangsungkan perkawinan poligami, seorang suami harus mendapat izin dari pengadilan dengan alasan yang terbatas dan syarat-syarat yang ketat. Tanpa izin hukum dari pengadilan, praktik poligami akan berimplikasi pada hukum positif di Indonesia. Oleh karena itu, tujuan dari penelitian ini adalah untuk mengetahui implikasi dari praktik poligami terhadap hukum positif di Indonesia. Akibatnya, praktik poligami dapat berdampak pada sistem hukum pidana dan perdata Indonesia.Kata kunci: Poligami; Hukum Islam; hukum positif